Rethinking biodiversity governance in European agricultural landscapes: Acceptability of alternative governance scenarios. (September 2018) - Velten, Sarah; Schaal, Tamara; Leventon, Julia; Hanspach, Jan; Fischer, Joern; Newig, Jens
Highlights: Consideration of changes in the governance system for biodiversity management. Use of scenarios to explore the acceptability of alternative governance approaches. Highlighting of strengths and weaknesses of existing governance approaches. Improved biodiversity outcomes require fundamental changes to the governance system. A widely acceptable governance approach needs to be a hybrid of different approaches. Abstract: Biodiversity conservation in agricultural landscapes continues to be a key challenge in the European Union (EU). However, to date the Common Agricultural Policy (CAP), which is central for addressing this issue, has proven ineffective in improving biodiversity outcomes. In contrast to solutions that focus on individual policies or measures, we take a holistic approach to explore changes in the broader governance system for biodiversity conservation. For this purpose, we draw on a set of four theoretical, ideal-typical scenarios which represent alternative governance approaches and used them to stimulate discussion about the acceptability of contrasting governance approaches among a broad range of actors in three case study areas in Germany and Sweden. Our results highlight that acceptability of alternative governance approaches is shaped by a large variety of factors. Additionally, despite differences between the views and interests of different stakeholder groups, our findings show universal support for governance approaches that fundamentally differ from the status quo approaches. Thus, evaluating and addressing acceptability of alternative governance approaches needs to consider the preferences of many different stakeholders and requires a more holistic perspective. We therefore argue that designing a potentially widely acceptable alternative governance solution for biodiversity conservation in agricultural landscapes requires a blend of different governance approaches. We outline principles that can guide the design of such a blended governance approach and discuss key challenges arising from the suggested changes for both practitioners and future research.